2017
DOI: 10.1016/j.athoracsur.2017.04.035
|View full text |Cite
|
Sign up to set email alerts
|

Sequential Extended Thoracoscopic Sympathicotomy for Palmo-Axillo-Plantar Hyperhidrosis

Abstract: Sequential extended thoracoscopic sympathicotomy proved to be an effective method for the treatment of combined HH because it achieved satisfactory and sustained improvement of palmar, axillary, and plantar sweating. Although the benefits of sequential extended thoracoscopic sympathicotomy outweigh its drawbacks and technical difficulties, further prospective studies are required to ascertain the effectiveness of this new technique.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…Palmar HH reportedly affects manual activities and handling objects such as knitting, driving, opening doors, playing sports, hand shaking, electrical shocks in those with mechanical occupations, and corrosion of commonly touched objects [ 31 ]. In one study, patients with plantar HH had impairment of physical tasks such as putting on socks, wearing sandals, and walking barefoot as identified by elevated Keller scores, a tool used to measure pre- and post-operative QoL in patients receiving sympathectomy [ 17 , 32 ]. Other symptoms of plantar HH include instability of feet using open shoes or heels, sprains, formation of sweat puddles, and a frequent need to change socks [ 19 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Palmar HH reportedly affects manual activities and handling objects such as knitting, driving, opening doors, playing sports, hand shaking, electrical shocks in those with mechanical occupations, and corrosion of commonly touched objects [ 31 ]. In one study, patients with plantar HH had impairment of physical tasks such as putting on socks, wearing sandals, and walking barefoot as identified by elevated Keller scores, a tool used to measure pre- and post-operative QoL in patients receiving sympathectomy [ 17 , 32 ]. Other symptoms of plantar HH include instability of feet using open shoes or heels, sprains, formation of sweat puddles, and a frequent need to change socks [ 19 ].…”
Section: Resultsmentioning
confidence: 99%
“…Palmar HH reportedly affects manual activities and handling objects. Elalfy et al 2017 [ 32 ] Keller Pre-post interventional study 42 Patients with palmo-axillo-plantar HH had elevated Keller scores in all domains plantar (i.e., impairment in tasks such as putting on socks, wearing sandals, and walking barefoot), axillary, and palmar. Shayesteh et al 2017 [ 33 ] HDSS, SF-36 Retrospective study 188 5.5% sought medical healthcare help for problems.…”
Section: Methodsmentioning
confidence: 99%
“…Better visualization of the stellate ganglion and its preservation to avoid development of post-operative Horner's syndrome. [11] As noted in many studies, the plantar domain affects considerable part of those patients of about 45% [4]; while others reported incidence of plantar domain of 70 to 100 % of patients with primary hyperhidrosis; latter researchers used extended technique of ablation from R3 to R12 to manage those cases [12]. In the Society of Thoracic Surgeons 2011 Expert Consensus for the Surgical Treatment of Hyperhidrosis [13], no recommendations for plantar domain management were noted.…”
Section: Discussionmentioning
confidence: 99%
“…Concerning the importance of the palmo-plantar type, the plantar domain affects considerable part (about 45%) of those patients with PH [4]. Other studies reported incidence of plantar domain of 70 to 100% in patients with PH; the latter researchers used extended technique of ablation from R3 to R12 to manage those cases [25]. In the Society of Thoracic Surgeons 2011 Expert Consensus for the Surgical Treatment of Hyperhidrosis [26], no recommendations for plantar domain management were noted.…”
Section: Discussionmentioning
confidence: 99%